Chemical and biological profiles of essential oil from different parts of myrtus communis l. Subsp. communis from turkey - (:unkn) unknown (University of Zagreb, 2020)
The present study reports chemical composition, antidiabetic, anti-inflammatory and antioxidant potential of essential oils from leaves and twigs of Myrtus communis L. subsp. communis from Turkey. Essential oils were obtained separately from leaves and twigs of Myrtus communis subsp. communis (MC) by hydrodistillation using a Clevenger-type apparatus. Chemical compositions were determined using GC/MS. Antidiabetic, anti-inflammatory and antioxidant activities of essential oils were tested by α-amylase inhibitory, 5-lipoxygenase inhibitory and DPPH/ABTS radical scavenging methods, respectively. The major compounds of essential oil of Myrtus communis subsp. communis leaves (MCLEO) were α-pinene (35.6%), 1,8-cineole (28.3%), linalool (10.5%), and limonene (8.2%), while the major constituents of essential oil of Myrtus communis subsp. communis twigs (MCTEO) were α-pinene (30.7%), 1,8-cineole (23.5%), p-cymene (13.3%) and limonene (11.9%). MCLEO and MCTEO showed good and moderate radical scavenging activity with IC50 values of 124.40 µg/mL and 390.10 µg/mL for ABTS radical, respectively. MCLEO and MCTEO exhibited significant radical scavenging activity with IC50 values of 34.13 µg/mL and 28.15 µg/mL for DPPH radical, respectively. Also, MCLEO and MCTEO displayed strong and good antidiabetic activity with IC50 values of 29.94 µg/mL and 159.80 µg/mL against α-amylase enzyme, respectively. Finally, MCLEO and MCTEO showed good anti-inflammatory activity with IC50 values 86.10 µg/ mL and 96.55 µg/mL against 5-lipoxygenase enzyme, respectively. From the present study it can be concluded that essential oils, especially MCLEO, possess good antidiabetic, anti-inflammatory and antioxidant activities. Also, this is the first study on chemical composition of MCTEO from Turkey, as well as on α-amylase inhibitory and 5-lipoxygenase inhibitory activities of MCLEO and MCTEO. © 2020, University of Zagreb. All rights reserved.
Keywords: Anti-inflammatory activity; Antidiabetic activity; Antioxidant activity; Communis; Essential oil; Myrtus communis subsp